ZionimeArt App: Designing Mobile Application as A Medium For Selling Anime T-shirts - Eddy Soeryanto Soegoto; Novia Aenu Rizqi; Iluh Sri Purwani; Zanjabil Zulkarnain (Universitas Komputer Indonesia, 2022)
Technology and information media is currently experiencing a rapid development, this is seen from the use of technology media as a tool in various aspects of life and one of them is the development of applications as a place to buy and sell a product. The purpose of designing this application is as a place / information system that can help the public in finding and buying reliable Japanese anime T-shirts, in addition this application is also a promotional media with the marketing segment of anime T-shirts. This research used qualitative descriptive analysis method with High fidelity prototyping and SDLC method. The development of ZionimeArt application can make it easier for people especially anime fans to easily find and buy various types of anime T-shirts in one place. In addition, because of the concept of a mobile application, it can facilitate users in accessing the site under any conditions easily and efficiently. ZionimeArt itself has the main purpose as a special application for the sale of various types of anime T-shirts, with a display that presents a wide selection of clothing types up to the purchase process. With this, the purpose and function of this application is to help and overcome the difficulties of the community in finding different types of anime T-shirts. It can be concluded, ZionimeArt application is an intermediary media between the community and anime products that they like, so they can buy it easily.